Self-CATA: a new consumer test approach with descriptors ranked by Stepwise Discriminant Analysis (Research, Society and Development, 2023)
The self-CATA test proposed in this study allows consumers an opportunity to supplement the CATA terms with additional vocabulary from a previously generated standard list. Considering that some attributes listed on the CATA test are frequently unselected by consumers because most of them were provided by a previous sensory descriptive panel, even from instrumental or texture parameters, a consensus list to obtain a complete product characterization could be created: a self-own vocabulary list. The work´s design was developed using a CATA-questionnaire containing descriptors provided from a previous panel, ranked by Stepwise Discriminant Analysis to which the consumer’s new repertory was added. In this regard, six raspberry gelatin samples were evaluated by 120-consumers using the self-CATA questionnaire. Results indicated eight new consumer features, not previously verified, such as pink color and odd and metallic flavors. The key-point of this study is to verify a significant choice of CATA terminology.